Real-world evaluation of an evidence-based telemental health program for PTSD symptoms - Jocelynn T. Owusu; Lu Wang; Shih-Yin Chen; Robert E. Wickham; Scott T. Michael; Nazneen F. Bahrassa; Alethea Varra; Jennifer L. Lee; Connie Chen; Anita Lungu (Scientific Reports)
Abstract Blended care therapy (BCT), which augments live, video-based psychotherapy sessions with asynchronous digital tools, has the potential to increase access to evidence-based treatments for posttraumatic stress disorder (PTSD). However, its effectiveness in diverse, real-world settings is not well-understood. This evaluation aimed to assess clinical outcomes of a BCT program for PTSD symptoms. A retrospective cohort analysis was conducted of 199 adults who received an employer-offered BCT program for PTSD symptoms that delivered either cognitive processing therapy or prolonged exposure. PTSD symptom severity was regularly assessed using the PTSD Checklist for DSM-5 (PCL-5). Growth curve models were used to evaluate the trajectory of PTSD symptoms over the course of care, and an interaction term was added to assess outcomes by baseline PTSD symptom severity (i.e., PCL-5 ≥ 31 versus PCL-5 < 31). End-of-care reliable improvement and recovery were evaluated. On average, participants with baseline PCL-5 < 31 exhibited statistically significant declines in PTSD symptoms during care, while participants with baseline PCL-5 ≥ 31 showed statistically significantly steeper initial declines in PTSD symptoms that became less pronounced over time. Overall, 82.91% of participants demonstrated either reliable improvement or recovery in PTSD symptoms. This evaluation suggests BCT for PTSD symptoms can be beneficial in real-world settings. Future research should perform large-scale evaluations.